UNMET NEED FOR HEALTHCARE AMONG PEOPLE WITH HYPERTENSION IN INDONESIA - Asmaripa Ainy; Amrina Rosyada; Haerawati Idris; Asri Maharani (Universitas Airlangga, 2022)
Background: Hypertension is a worldwide public health problem, mainly due to its high frequency and risks leading to cardiovascular diseases. The prevalence of hypertension in the Indonesian population aged > 18 years in 2018 was 34.11%. The unmet need for healthcare has generally been explored in most empirical studies concerning people with hypertension. Aims: This study investigated the determinants of unmet needs for healthcare among people with hypertension. Methods: The design of this study was cross-sectional on data from the Indonesian Family Life Survey wave 5 (IFLS-5). The survey sample was 6,302 adults aged > 40 years stratified by rural/urban residence status. A three-level multilevel analysis was performed to estimate the individual, household, and community-level determinants of unmet needs for hypertension care. Results: As many as 78.4% of the respondents with hypertension reported unmet needs for healthcare. Age, female, single, income, having insurance, urban residence, and the number of health-integrated posts for the elderly (Posyandu Lansia) were significantly associated with umeet needs for healthcare utilization among people with hypertension, while education and employment status showed no association with these variables. Conclusion: Improvement in access to healthcare and reduction in health inequality is required to address this problem.